Trade and industry in early modern Italy - Sella, Domenico (Variorum collected studies series, 2009)
This volume brings together a set of classic essays by Domenico Sella in which he reassesses the economic fortunes of Northern Italy, in particular Lombardy and Venice, during the 16th and 17th centuries